MicroRNA Cluster 302–367 Enhances Somatic Cell Reprogramming by Accelerating a Mesenchymal-to-Epithelial Transition - Liao, Baojian (American Society for Biochemistry and Molecular Biology, 2011)
MicroRNAs (miRNAs) are emerging critical regulators of cell function that frequently reside in clusters throughout the genome. They influence a myriad of cell functions, including the generation of induced pluripotent stem cells, also termed reprogramming. Here, we have successfully delivered entire miRNA clusters into reprogramming fibroblasts using retroviral vectors. This strategy avoids caveats associated with transient transfection of chemically synthesized miRNA mimics. Overexpression of 2 miRNA clusters, 106a–363 and in particular 302–367, allowed potent increases in induced pluripotent stem cell generation efficiency in mouse fibroblasts using 3 exogenous factors (Sox2, Klf4, and Oct4). Pathway analysis highlighted potential relevant effectors, including mesenchymal-to-epithelial transition, cell cycle, and epigenetic regulators. Further study showed that miRNA cluster 302–367 targeted TGFβ receptor 2, promoted increased E-cadherin expression, and accelerated mesenchymal-to-epithelial changes necessary for colony formation. Our work thus provides an interesting alternative for improving reprogramming using miRNAs and adds new evidence for the emerging relationship between pluripotency and the epithelial phenotype.